Debt management practices of newly married couples - Fajarillo, Anne Marie J.; Trio, Consuelo Q. (2006.)
The study aimed to determine the debt management practices of newly married couples in terms of: the spouse in-charge of loaning decisions, reasons for acquiring and using credit cards, sources of loans/credit, amount of loans/credit, payment practices and prevalence of debt-related problems. Data were collected from 105 couples married within the last ten years using the Debt Management Questionnaire. Spouses make joint decisions on matters regarding acquisition of loans for all types of expenses. The top four reasons for acquiring and using credit cards include convenience, emergencies, security and special occasions purposes. The usual sources of credit include credit cards, personal and formal sources of credit. Credit cards are used for food expenses and emergency purposes. Personal sources of credit are used for emergencies, medical and education purposes. Formal sources of credit on the other hand, are used for big ticket items like car and housing loans. In terms of amount, car and housing loans ranked the highest while amount of loans from moneylenders is the lowest. Majority of newly married couples allocate at least 10 to 20 percent of their monthly income for debt payment. In general, a large percentage of the couples practice good payment practices. Furthermore, debt-related problems, very seldom occur among newly married couples. However, when problems do occur, the top three prevalent situations include 1) not having enough money to pay debts when due, 3) borrowing money to pay other debts. The least prevalent is credit card companies going after them.
Thesis (BS Home Economics)--University of the Philippines Diliman.
Keywords: Married people; Finance, Personal